KARAKTERISTIK-KARAKTERISTIK DASAR PEMBAYAR DIVIDEN - Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Financial factors is still the basic consideration for most companies to decide their dividend policy. Generally, dividend policy is a reflection of successful financial performance by companies in terms to perform profitability, investment opportunities, and size, related to basic financial factors which are assets, liabilities, and equities. The objective of this study is to give the empirical evidence about the relationship of basic financial factors with dividend policy. The study taking 373 listed companies in Indonesia Stock Exchange in period of 2010 till 2012, and using multinomial logistic regression for hypothesis testing. This study is find that, expect fixed assets, total assets, total liabilities, retained earnings, revenue and net earnings have significant effect to dividend policy, while fixed assets has not significant effect to dividend policy.